DNA Vaccination Affords Significant Protection against Feline Immunodeficiency Virus Infection without Inducing Detectable Antiviral Antibodies - Hosie, Margaret J. (American Society for Microbiology (ASM), 1998)
To test the potential of a multigene DNA vaccine against lentivirus infection, we generated a defective mutant provirus of feline immunodeficiency virus (FIV) with an in-frame deletion in pol (FIVΔRT). In a first experiment, FIVΔRT DNA was administered intramuscularly to 10 animals, half of which also received feline gamma interferon (IFN-γ) DNA. The DNA was administered in four 100-μg doses at 0, 10, and 23 weeks. Immunization with FIVΔRT elicited cytotoxic T-cell (CTL) responses to FIV Gag and Env in the absence of a serological response. After challenge with homologous virus at week 26, all 10 of the control animals became seropositive and viremic but 4 of the 10 vaccinates remained seronegative and virus free. Furthermore, quantitative virus isolation and quantitative PCR analysis of viral DNA in peripheral blood mononuclear cells revealed significantly lower virus loads in the FIVΔRT vaccinates than in the controls. Immunization with FIVΔRT in conjunction with IFN-γ gave the highest proportion of protected cats, with only two of five vaccinates showing evidence of infection following challenge. In a second experiment involving two groups (FIVΔRT plus IFN-γ and IFN-γ alone), the immunization schedule was reduced to 0, 4, and 8 weeks. Once again, CTL responses were seen prior to challenge in the absence of detectable antibodies. Two of five cats receiving the proviral DNA vaccine were protected against infection, with an overall reduction in virus load compared to the five infected controls. These findings demonstrate that DNA vaccination can elicit protection against lentivirus infection in the absence of a serological response and suggest the need to reconsider efficacy criteria for lentivirus vaccines.